The Italian Society of Health Horizon Scanning (SIHHS) (Italian Journal of Public Health, 2010)
The Italian Society of Health Horizon Scanning (SIHHS) was created on May 4th, 2009, in Naples. The SIHHS’ main objective is to poll together and try to forecast the demand for technology products through the networking of professionals from regional healthcare units, universities and local Departments in Campania and Italy. Furthermore, the SIHHS intends to establish a set of clinical recommendations to be operatively used as strategic guidelines to enhance and promote their adoption within clinical and organizational settings. The general aim is to modernize the healthcare system through the design and/or the experimentation of innovative clinical, organizational and managerial models, efficaciously responding to healthcare needs, and contemporarily ensuring that the appropriate levels of benefits have been achieved, while minimizing risks and maximizing efficiency.
Keywords: Health horizon scanning; technology products; nexialist; guidelines